Kecerdasan emosi dan motivasi kerja dalam kalangan subordinat MARDI - Amira Wahid; Muhammad Ajib Abd Razak; Fatimah Yusooff (Penerbit Universiti Kebangsaan Malaysia, 2016)
The objective of this study is to identify whether emotional intelligence among employees between grades N17 to N27 substantially affects their work motivation in the organisation of Mardi. This study used the instruments of Emotional Competence Inventory (ECI) and Employee Performance Measure. Data were collected by using questionnaires that were distributed to 50 staffs in Human Resources Management Division, Headquarters of MARDI, Serdang, Selangor. The results of correlation analysis showed that the relationship between emotional intelligence and motivation among employees in Grade 17 to 27 that are working in MARDI is not significant. In addition, the different levels of emotional intelligence according to their positions were not significant, however, for different levels of self-motivation by grade showed a significant and positive relationship. The research findings can give a good benefit to MARDI Division Human Resources Management in the effort of improving the quality of work and services among support staffs.